ANALISIS TINGKAT KEPUASAN UNIT KEGIATAN MAHASISWA DAN ORGANISASI MAHASISWA TERHADAP PERAN LAYANAN KEMAHASISWAAN - Adryan Novanda; Annas Al Mudzakir; Nabilah Sri Rejeki (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this study was to find out the role of student services and to analyze the satisfaction of UKM (Student Activity Units) and ORMAWA (Student Organizations) with the services provided by the student affairs bureau at Djuanda University, Bogor. This type of research is descriptive research with a mixed method approach. That is a combination of qualitative and quantitative research that is used together with the aim of obtaining more comprehensive, valid and objective data. The data collection technique used in this study was interviewing the head of the Djuanda University student bureau and completing a questionnaire by each head of the Student Activity Unit and Student Organizations at Djuanda University which would then be converted into qualitative information. The results of the study are described as follows: (1) Based on the results of the questionnaire analysis using a Likert scale, there is a total of 68.7% of respondents' satisfaction which illustrates that the level of satisfaction of the management of the Student Activity Unit and Student Organizations at Djuanda University is within category "satisfied" with an interval of 51% - 75%. And (2) Through observations and interviews conducted in this study, it was found that the role of student services carried out by the student bureau towards Student Activity Units and Student Organizations at Djuanda University, Bogor, has a fairly important role because everything and activities carried out by the Student Activity Unit and Student Organizations will always be supervised by the Student Affairs Bureau so that everything can be well organized. Based on the results of this study, it is hoped that the student affairs bureau of Djuanda University will always improve services to the Student Activity Unit and Student Organizations at Djuanda University so that all activities carried out by the Student Activity Unit and Student Organizations can be well organized